2020
DOI: 10.21031/epod.683176
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Turkish Version of Aggression Questionnaire Short Form: Measurement Invariance and Differential Item Functioning across Sex and Age

Abstract: The aim of the present study was to test the psychometric properties of the Aggression Questionnaire Short Form for adolescents and adults in Turkish. The adaptation study was conducted with 778 adolescents aged between 15-18 and 1067 adults aged between 19 and 44. The construct validity of the questionnaire was tested via Parallel Analysis, Exploratory Factor Analysis and Confirmatory Factor Analysis. Furthermore, item-total correlations, test-retest score correlation, and internal consistency (Cronbach Alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…Participants respond to each item on the scale as "Totally wrong", "Mostly wrong", "Neither wrong nor right", "Mostly right", and "Completely right". In the original study, the total Cronbach's alpha value was found to be 0.80, and 0.76 for physical, 0.68 for verbal, 0.70 for anger, and 0.74 for hostility sub-dimensions (Bryant & Smith, 2001;Kuzucu & Ertürk Sarıot, 2020). The Cronbach's alpha value of the scale was found to be 0.911 and 0.806 for physical, 0.805 for verbal, 0.857 for anger, and 0.867 for hostility subdimensions.…”
Section: The Aggression Scale: Short Formmentioning
confidence: 95%
“…Participants respond to each item on the scale as "Totally wrong", "Mostly wrong", "Neither wrong nor right", "Mostly right", and "Completely right". In the original study, the total Cronbach's alpha value was found to be 0.80, and 0.76 for physical, 0.68 for verbal, 0.70 for anger, and 0.74 for hostility sub-dimensions (Bryant & Smith, 2001;Kuzucu & Ertürk Sarıot, 2020). The Cronbach's alpha value of the scale was found to be 0.911 and 0.806 for physical, 0.805 for verbal, 0.857 for anger, and 0.867 for hostility subdimensions.…”
Section: The Aggression Scale: Short Formmentioning
confidence: 95%